Predictive Value of Circulatingve-catherin in Coronary Artery Disease Patients with Symptomatic Moderate to Severe Chronic Heart Failure - Berezin, Alexander E; Kremzer, Alexander A; Samura, Tatayna A (Journal of Medicine, 2015)
Aim: To evaluate the prognostic value of circulating VE-catherinfor cumulative survivalin patients with ischemic chronic heart failure (CHF). Methods: A total of 154 patients withischemic symptomatic moderate-to-severe CHF were enrolled in the study on discharge from the hospital. Observation period was up to 3 years. Blood samples for biomarkers measurements were collected. ELISA method for measurements of circulating level of VE-catherin was used. Concentrations of VEcatherinfor cumulative survival cases due to advanced CHF were tested. Additionally, all-cause mortality, and CHFrelated death were examined. Results: During a median follow-up of 2.18 years, 21 participants died and 106 subjects were hospitalized repetitively. Medians of circulating levels of VE-catherin in survived and died patient cohort were 0.63 ng/ml (95% confidence interval [CI] = 0.55-0.64 ng/ml) and 1.03 ng/ml (95% CI = 0.97-1.07 ng/ml) (P<0.001). ROC analysis has been shown that cutoff point of VE-catherin concentration for cumulative survival function was 0.755ng/ml. It has beenfound a significantly divergence of Kaplan-Meier survival curves in patients with high (>0.755 ng/ml) and low (<0.755 ng/ml) concentrations of VE-catherin. Circulating VE-catherin independently predicted all-cause mortality (OR = 1.27; 95% CI = 1.081.59; P = 0.002), CHF-related death (OR = 1.16; 95% CI 1.021.50; P < 0.001), and also CHF-related rehospitalisation (OR = 1.12; 95% CI = 1.07 1.25; P<0.001) within 3 years of observation period. Conclusion: Increased circulating VE-catherinassociates with increased 3-year CHF-related death, all-cause mortality, and risk for recurrent hospitalization due to CHF. J MEDICINE July 2015; 16 (2) : 73-78